The potential roles of galectin-3 in AKI and CKD - Wang, Fengyun; Zhou, Lixin; Eliaz, Amity; Hu, Chang; Qiang, Xinhua; Ke, Li; Chertow, Glenn; Eliaz, Isaac; Peng, Zhiyong (Frontiers in Physiology, 2023)
Acute kidney injury (AKI) is a common condition with high morbidity and mortality and is associated with the development and progression of chronic kidney disease (CKD). The beta-galactoside binding protein galectin-3 (Gal3), with its proinflammatory and profibrotic properties, has been implicated in the development of both AKI and CKD. Serum Gal3 levels are elevated in patients with AKI and CKD, and elevated Gal3 is associated with progression of CKD. In addition, Gal3 is associated with the incidence of AKI among critically ill patients, and blocking Gal3 in murine models of sepsis and ischemia-reperfusion injury results in significantly lower AKI incidence and mortality. Here we review the role of Gal3 in the pathophysiology of AKI and CKD, as well as the therapeutic potential of targeting Gal3.